Towards understanding the influence of personality and team behaviors on requirements engineering activities - Norsaremah Salleh; Badamasi Imam Ya'u; Azlin Nordin (Institute of Advanced Engineering and Science, 2023)
Requirements engineers play an important role in the development of software products and services. The nature of requirements engineering (RE) is multifaceted and influences the quality, success, or failure of software products. In gathering software requirements, engineers commonly work in a team, particularly when dealing with the customers or modeling the requirements, hence the team behavior may influence the RE activities. The investigation of requirements engineers’ personality and their team behavior associated with RE activities is still an open area in which research is still developing. This study aims to investigate the personality and team behavior of requirements engineers involved in RE activities using a systematic literature review approach. We included 64 primary studies that addressed the association between personality and team behavior of requirements engineers on the effectiveness of RE activities. The result shows that among personality dimensions, extraversion and conscientiousness were found to be the predominant personality traits that positively affect RE activities. Furthermore, team behavior of requirements engineers such as flexibility, collaboration, creativity, innovation, and norms were discovered as factors that influence the RE process, performance, and success. The findings of this study contribute to the body of knowledge and practice of RE by providing empirical evidence on the influence of requirements engineers’ personality and team behavior on the effectiveness of RE activities.